Shell Model Calculations for Some Properties of 29-34Mg Isotopes - Mahmood, Lubna Abduljabbar; Flaiyh, Ghaith Naima (Iraqi Journal of Science, 2021)
The calculations of the shell model, based on the large basis, were carried out for studying the nuclear 29-34Mg structure. Binding energy, single neutron separation energy, neutron shell gap, two neutron separation energy, and reduced transition probability, are explained with the consideration of the contributions of the high-energy conﬁgurations beyond the model space of sd-shell. The wave functions for these nuclei are used from the model of the shell with the use of the USDA 2-body effective interaction. The OBDM elements are computed with the use of NuShellX@MSU shell model code that utilizes the formalism of proton-neutron.